A body-scaling approach to modifying sports equipment for children: a badminton-based experimental study - Jeffrey Low Fook (Tanjung Malim, 2023)
A body-scaling approach to modifying sports equipment for children: a badminton-based experimental study by Jeffrey Low Fook